ULTRASOUND STUDY OF PATIENTS WITH KELOID SCARS OF THE MAXILLOFACIAL AREA - D. S. Avetikov; O. P. Bukhanchenko; V. V. Aipert; K. P. Lokes (Проблеми екології та медицини)
Despite the possibility of modern surgery and dermatological cosmetology, the problem of differential diagnosis of patients with keloid scars remains relevant and significant at present. As clinical practice shows, not just the presents and the size of functional or aesthetic defect in scar tissue changes are important, but also the degree of their negative influence on the process of physical, psychological and social adaptation of the patient. The aim of our study was to optimize and improve the effectiveness of treatment of facial keloid scarring by identifying the type of scarred skin of the head and neck, and using ultrasound examination. The ultrasound method of investigation was performed on 50 patients with keloid scars of the head and neck. Clinical study of the general characteristics of the scar was supplemented by an additional analysis of the structural features of the cicatricial tissues by ultrasound examination. For the purpose of comparison, intact skin was used. Analysis of ultrasonography allowed to determine the color echogenic pattern of keloid scars, which differed substantially from the dermis of intact skin. Among the echogenic signs of postoperative keloid scarring, one should point out an increase in the depth of cicatrix of the tissue in comparison with the thickness of the intact derma, an average of 8-11%, an average thickness of the epidermis is 18-26%, a clear boundary between intact skin and keloid scar is traced, which is a clear differential sign of this type of scar. Only in 7% of cases, we have visualized the border with the hypodermis in the peripheral edges of the scar, which indicates the infiltration character of the growth of the keloid and again proves its similarity with the tumor. Today, there is no universal method for differential diagnosis of various types of scars of the head and neck. Therefore, it is necessary to develop an informative and economically expedient method of diagnostics. Ultrasonography of scarring is a non-invasive survey method that can objectively, informatively and safely evaluate numerous anatomical structures, determine the type and depth of scar formation.